Autobiographical memory loss in Alzheimer's disease: The role of the reminiscence bump. (May 2022) - Berntsen, Dorthe; Kirk, Marie; Kopelman, Michael D.
Abstract: Research on autobiographical memory loss in Alzheimer's disease (AD) is characterized by conflicting findings concerning a possible sparing of older memories. The literature shows evidence for both a negative temporal gradient, a flat gradient and a reminiscence bump – that is, a disproportionally high frequency of memories from early adulthood relative to surrounding periods. Here, we expanded the number of lifetime periods of the Autobiographical Memory Interview (AMI; Kopelman, Wilson & Baddeley, 1989, 1990) from the standard three to seven in order to increase the sensitivity of the test to variations in the temporal distribution of autobiographical memories across the life span. Twenty-five older adults diagnosed with AD ( M MMSE = 21.16, SD = 5.08) and a matched sample of 30 healthy, older adults were assessed. The temporal distribution for personal semantic information in AD showed a temporal gradient steadily decreasing from middle childhood to present life, consistent with predictions derived from consolidation theories. In comparison, the temporal distribution of incidents/episodic memories produced by AD patients in response to the expanded AMI showed a predominance of autobiographical memories from age 6 to 30, followed by a steep drop in memory referring to events that had occurred after age 30. This distribution challenges standard theories of retrograde amnesia in AD by showing neither a temporal gradient, decreasing progressively from early to later life, nor a flat gradient. In contrast, the distribution is consistent with the reminiscence bump identified in autobiographical memory research. Schematization and retrieval support provided by cultural life scripts are discussed.